Ciclos políticos eleitorais e investimentos das administraç\~oes públicas no Brasil - Rodrigo Octávio Orair; Raphael Rocha Gouvêa; Ésio Moreira Leal (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper provides new evidence for the empirical literature that investigates the presence of political cycles in public investments in Brazil. This approach differs from most of the studies for applying the state-space modeling whose greatest benefit is estimating the cyclical component endogenously and with greater precision. Another difference is that it considers the presence of cycles in central, states and local investments and central government capital transfers allowing a wider vision of the general government sector and of the intergovernmental relations. The main contributions come from the identification of qualitative differences among the political cycles of each government level - pointing to a smaller degree of direct influence of local elections as it progresses from local to state and central levels - and the close relation between the two-year cycles of central government transfers and of the investment of state and local levels.
Keywords: E39; E62; H54; H76; H77; 330; political cycles; public investment; space state models